Effect of electron beam irradiation on thermal and crystallization behavior of PP/EPDM blend - Balaji, Anand B.; Ratnam, Chantara Thevy; Khalid, Mohammad *; Walvekar, Rashmi (Elsevier, 2017)
The irradiation stability of ethylene-propylene diene terpolymer (EPDM)/ polypropylene (PP) blends is studied in an attempt to develop radiation compatible PP/EPDM blends suitable for medical applications. The PP/EPDM blends with mixing ratios of 80/20, 50/50/ 20/80 were prepared in an internal mixer at 165 °C and a rotor speed of 50 rpm followed by compression molding. The blends and the individual components were irradiated using 3.0 MeV electron beam (EB) accelerator at doses ranging from 0 to 100 kGy in air and room temperature. Later, the PP/EPDM blends were subjected to gel content, thermal stability, crystallization and dynamic mechanical properties before and after irradiation. Results revealed that the irradiation-induced crosslinking in the PP/EPDM blend increases with the increasing irradiation dose and the EPDM content in the blend. However, the thermal stability of the blends did not show any significant changes upon irradiation. The dynamic mechanical analysis shows that the EPDM rich blend has higher compatibility than PP dominant blends. A further improvement in the blend compatibility found to be achieved upon irradiation.